Nanofertilizer Possibilities for Healthy Soil, Water, and Food in Future: An Overview - Verma, Krishan K.; Song, Xiu-Peng; Joshi, Abhishek; Rajput, Vishnu D.; Singh, Munna; Sharma, Anjney; Singh, Rajesh Kumar; Li, Dong-Mei; Arora, Jaya; Minkina, Tatiana; Li, Yang-Rui (Frontiers in Plant Science, 2022)
Conventional fertilizers and pesticides are not sustainable for multiple reasons, including high delivery and usage inefficiency, considerable energy and water inputs with adverse impact on agro-ecosystem. Achieving and maintaining optimal food security is a global task that initiates agricultural approaches to be revolutionized effectively on time, as adversities in climate change, population growth, and loss of arable land may increase. Recent approaches based on nanotechnology may improve in vivo nutrient delivery to ensure the distribution of nutrients precisely, as nano-engineered particles may improve crop growth and productivity. The underlying mechanistic processes are yet to be unlayered because in coming years, the major task may be to develop novel and efficient nutrient uses in agriculture with nutrient use efficiency (NUE) to acquire optimal crop yield with ecological biodiversity, sustainable agri-produce, and agri-socio-economy. This paper highlights the potential of nanofertilizers in agricultural crops for improved plant performance-productivity incase subjected to abiotic stress conditions.